Determinants of Capital Structure on UK Quoted Companies - Vo, Hai Tuan (2012)
The dissertation aims to examine the determinants influencing the capital structure decisions on UK listed firms and identify which theory is the most relevant one toward UK companies. A panel data set of 234 firms from 9 different industries on FTSE 350 was recorded from 2002-2012 to analyze the factors affecting capital structure. The one-way ANOVA is employed to validate whether the industry effects importantly seize any influence in explaining firms’ debt ratios. Moreover, statistical tests are adopted to carefully determine the most applicable approach to model the relationships between capital structure’s determinant and debt ratio. Each test is conducted on the book value of long-term & short-term debt ratios as dependent variables. The explanatory variables such as profitability, size, growth opportunity, tangibility, non-debt tax shield, and effective tax rate and industry classification are thoroughly examined. Based on the result, most of the determinants tend to follow the trade-off theory. Tangibility, firm size, non-debt tax shield indicate and industry classification indicate a significantly positive impact upon the firms’ debt. On the other hand, profitability, effective tax rate and growth opportunity do not provide any statistical explanation for UK firms’ financing decisions. In fact, there is no evidence to conclude that which theory is superior to the other. Therefore, the relationship between leverage and determinants of capital structure still remains as a puzzle in the literature of finance.